Kualitas Pelayanan Kantor Kelurahan Kedaung Kota Tangerang Selatan. - Nimas Arum P.S; Mawar Mawar (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This Study examines the low quality of public service provided by Kedaung Village officials,Lack of public knowloedge regarding public service,procedures in kedaung Village,lack of response and attention from Kedaung Village officials to people who need service in Kedaung Village.the purpose of the research is to find out and analyze more broadly regarding the quliy of service at the Kedaung Vilage,south Tangerang City.The Method used in this study is a descriptive qualitative approach that aims to describe service at the Kedaung Village office.The results of this study use the service quality theory of Zeithaml Berry and Prasurahman,namely Tangible (Direct evidence),Realibility (realibility),Responsiveness (responsiveness),Assurance (guarantee),Empathy (empathy).This shows that the service at the kedaung sub-district office has not run perfectly.On the Realibility indicator,it has not run perfectly,such as the expertise of officers in using supporting facilities in the service process. On the responsiveness indicator,all officer who carry out service are classified as responsive to the community who want perform service or people who have complaints about the ongoing service process.